Applying boron to coconut palm plants: effects on the soil, on the plant nutritional status and on productivity boron to coconut palm trees - Moura, J. Z.; Prado, R. M. [UNESP]; Benvindo, R. N.; Alencar, L. Chaves (Soc Chilena Ciência Suelo, 2013)
Boron, one of the micronutrients frequently found in low levels in tropical soils affects nutrition and productivity of coconut palm trees essentially cultivated in tropical climates. The objective of this research study was to evaluate the effect of boron on the nutritional status of the plant and its productivity when artificially applied to the culture soil. The experiment was carried out in a four year old, artificially irrigated, dwarf coconut palm orchard in Brazil, between January, 2005 and October, 2006. The soil was a red yellow Latosol (B: 0.18 mg dm(-3)). The treatments consisted in the application of five boron dosages: zero, 1, 2, 4, and 6 kg ha(-1). In the field, the treatments were arranged according to a completely randomized block design, with four replications. Boron (borax) dosages were applied in equal halves directly into the soil in the months of January and February of 2005. Boron concentration in the soil and plant and plant productivity were evaluated. The higher palm tree production was associated to levels of 0.6mg dm(-3) of B in the soil and 23.5mg kg(-1) in leaves. Ninety five percent of palm trees maximum production was obtained with the use of a boron dosage of 2,1kg ha(-1).
Keywords: Cocos nucifera L; Mineral nutrition; Micronutrients